The Effect of Customer Experience on Customer Satisfaction by Creating Sustainable Profit - Nerissa Arviana; Tantri Yanuar Rahmat Syah (Budapest International Research and Critics University, 2022)
This research has examined the relationship between customer satisfaction and experience with staff services. The purpose of this study is to determine the effect of customer satisfaction on service staff. The object of this research is customers who like to shop offline through physical stores or malls and online through market places such as Tokopedia, Shopee and Lazada. This study uses a quantitative approach using a questionnaire measuring instrument with a sample of 200 respondents using convenience sampling technique. In analyzing the data used univariate cell-mean test and multiple linear regression test. The results of this study concluded that staff does not affect the customer experience. In this research it can be concluded that service staff will have a positive influence on consumers in shopping back to good staff.